Along-wind and across-wind coupling analysis of high-rise buildings: Modeling and parameter identifications. (15th June 2023) - Liu, Zhen; Hui, Yi; Yang, Qingshan; He, Yuncheng
Abstract: High-rise buildings, with similar natural frequencies of sway modes in two orthogonal directions, can have coupled vibrations when exposed to strong wind exhibiting complex fluid-structure interaction and aero-elastic effects. This paper studies this coupled vibration with proposing of a mathematical model for both the in-plane and out-of-plane self-excitation force. A single-degree-of-freedom (SDOF) and two-degree-of-freedom (2DOF) aero-elastic square section high-rise building models are tested in wind tunnel to provide data for the analytical modeling. A new strategy to estimate the aerodynamic parameters and self-excitation forces is proposed. Parametric studies show that the self-excitation forces of the SDOF and 2DOFs models have significant difference. The out-of-plane self-excitation force acting in the along-wind direction induced by the across-wind vibration can become dominating inducing large amplitude vibration in the along-wind direction. The wind induced coupling vibrations for other tall buildings can similarly be studied in detail with the proposed strategy. Highlights: Wind tunnel experiment is carried out using aero-elastic tall building model. The along- and across-wind coupling effect of tall building is clearly checked. A mathematical model of the coupling self-excitation force is established. The identification method of system parameters and excitations is introduced. The characteristics of self-excitation force and buffeting force are discussed.